Pengaruh Suhu dan Tekanan terhadap Hasil Penggorengan Keripik Pisang Muli (Musa acuminata) Model Semprong Menggunakan Vacuum Frying - Asmara, Sandi; Oktafri, Oktafri; Kuncoro, Sapto; Sari, Selvi Yunita (Jurnal Agricultural Biosystem Engineering, 2024)
Fruit chips are healthy snacks because of their high fiber content. Processing of Muli banana chips with vacuum frying is an appropriate method to increase the shelf life of bananas by processing them into fruit chips. Utilization of Muli bananas with the semprong model as a processed product for chips is an effort to increase the diversification of Muli banana products and effort the selling value of the Muli banana products themselves. Vacuum frying is a frying process that can maintain nutritional value. The research method used experimental design in the form of a factorial Completely Randomized Design (CRD). Experimental factors in this study used two temperature factors (T), namely temperature 80°C, 85°C, 90°C, and pressure (P) during the frying process namely -68 cmHg, -70 cmHg and -72 cmHg, with 3 repetition. The parameters observed in this study were of material shrinkage (yield), moisture content, organoleptic test, and storage (estimation of material shelf life). The conclusion the quality of the Semprong model Muli banana chips with a temperature of 85°C and a frying pressure of -72 cmHg in this study produced good quality Muli banana chips. Muli banana chips of the semprong model with a temperature of 85°C and a frying pressure of -72 cmHg in this study had a material yield value of 30.3%, a moisture content of 3.94% and a crispness test score of 4.67 (crunchy), aroma of 3.93 (rather strong banana aroma), color 3.87 (brownish yellow), taste 4.73 (sweet). Keywords : Chips, Muli Banana, Vacuum Frying.